Impact of telehealth interventions on physiological and psychological outcomes in breast cancer survivors: A meta-analysis of randomised controlled trials - Ajmera, Puneeta; Miraj, Mohammad; Kalra, Sheetal; Goyal, Ramesh K.; Chorsiya, Varsha; Shaik, Riyaz Ahamed; Alzhrani, Msaad; Alanazi, Ahmad; Alqahtani, Mazen; Miraj, Shaima Ali; Pawaria, Sonia; Mehta, Vini (Frontiers in Oncology, 2023)
Introduction: The use of telehealth interventions has been evaluated in different perspectives in women and also supported with various clinical trials, but its overall efficacy is still ascertained. The objective of the present review is to identify, appraise and analyze randomized controlled trials on breast cancer survivors who have participated in technology-based intervention programs incorporating a wide range of physical and psychological outcome measures. Material and methods: We conducted electronic search of the literature during last twenty years i.e., from 2001 till August 10, 2021 through four databases. Standardized mean difference with 95% confidence interval was used. Results: A total of 56 records were included in the qualitative and 28 in quantitative analysis. Pooled results show that telehealth interventions were associated with improved quality of life (SMD 0.48, 95% CI 0.03 to 0.92, p=0.04), reduced depression (SMD -1.27, 95% CI =-2.43 to -0.10 p=0.03), low distress and less perceived stress (SMD -0.40, 95% CI =-0.68 to -0.12, p=0.005). However, no significant differences were observed on weight change (SMD -0.27, 95% CI =-2.39 to 1.86, p=0.81) and anxiety scores (SMD -0.09, 95% CI =-0.20 to 0.02, p=0.10) between the two groups. Improvement in health care competence and fitness among participants was also reported. Conclusion: Study concludes that telehealth care is a quick, convenient and assuring approach to breast cancer care in women that can reduce treatment burden and subsequent disturbance to the lives of breast cancer survivors.